Analysis of Drug Logistics Planning at Medical Management Agency in Ambon City Health Office (Qualitative study) (Medico Legal Update, 2020)
In health services, the drug can save lives and improve health quality. So the provision of essential medicinesis mandatory and requires government support at all levels, both central, provincial and Regency/city. Theexistence of such support can be activities, budgets and commitments. The purpose of this research is toknow the system of drug planning in the technical implementation Unit of the Regional Office of Medicinemanagement in Ambon City Health office. This type of research is a qualitative study. Data collection isdone through in-depth interviews, observation and document study. Information collected from 6 peoplewho are involved in the management of drugs in the technical implementation Unit of the Regional Officeof the Department of Medicine of the city Health office in Ambon. The results showed that drug planninguses a special team with the calculation of drug needs using method of consumption. The emptiness andexcess medication are still common due to the change in public health centers affecting the drug prescribingpatterns. Therefore, it needs a good coordination between the planning team in the technical implementationUnit of the regional office of the District Health Care office in Ambon City with a doctor at the Public healthcenter in the area to be obedient in writing prescriptions according to the medication that has been ordered.